eSports as a new playground - Baltezarevic, B.; Baltezarevic, V. (Facta Universitatis: Series Physical Education and Sport, 2019)
With the emergence of digital media, traditional sport got computer platforms as a new kind of gaming space. eSports, as a modern form of gaming, has become an inevitable part of the digital game culture. The aim of this research is to determine if there is a connection between playing eSports video games and sport knowledge, competition skills, social interaction, skill building for problem solving and pleasurable stimulation which leads to emotional well-being. The survey encompassed 256 respondents who filled out a questionnaire that provided answers to questions that enabled us to look at the attitudes of respondents who were tested in relation to the hypotheses set out in this paper. The research has shown that respondents believe that this type of game and the amateur competition has a positive impact on players and helps them advance their knowledge of sports, cognitive skills for competition and socialization, as well as helps them to feel good in the role of players.